Gynoecious inbred improves yield and earliness in cucumber (Cucumis sativus) - PATI, KALIDAS; MUNSHI, A D; BEHERA, T K; SUREJA, AMISH K (The Indian Journal of Agricultural Sciences, 2015)
Heterosis for yield and yield related traits were studied in 28 F1 hybrids of cucumber (Cucumis sativus L.) obtained by 8 × 8 diallel (excluding reciprocal) crosses involving eight parents including one gynoecious line (GBS-1). The F1 hybrids developed using gynoecious line as one parent were found to be superior in performance over top parents for various characters are GBS-1 × Pusa Uday for node number of first female flower (-2.61%), days to first female flower anthesis (-3.45 %), number of fruits/ plant (57.49 %) and yield / plant (66.40%) ,whereas GS-4 × Pusa Uday showed better heterosis for fruit length (20.34%), average fruit diameter (17.04 %) and average fruit weight (12.24%). The best three heterotic hybrids identified over the top parent for yield/plant GBS-1 × Pusa Uday (66.40%), GBS-1 × Punjab Naveen (54.44 %) and GS-4 × Pusa Uday (41.29%) and these may be exploited for commercial cultivation.